2017
DOI: 10.1007/s00405-017-4589-5
|View full text |Cite
|
Sign up to set email alerts
|

A study evaluating the effects of throat packs during nasal surgery: a randomised controlled trial

Abstract: The aims of this study were to identify differences in post-operative nausea and vomiting (PONV) and throat pain between throat packed and non-packed patient groups in nasal surgery. This was a prospective, double blind, randomised controlled trial. A water-soaked throat pack gauze was inserted in the mouth to occlude the oropharynx was used in the throat pack group. The second group received no throat pack. A validated PONV questionnaire was completed 6 h post-operatively. Visual analogue scores (VAS) for thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…14 Although pharyngeal pack is not universally adopted and is indeed rare in North America, 9 it has been a frequently used practice, especially in other European countries Turkey, Ireland, and so on as well as the United Kingdom, to minimize the risk of blood aspiration despite intubation cuff, as well as blood swallowing. 2,4 Previously, a review of pharyngeal pack usage for nasal surgery in 2009 assessed four randomized controlled trials and found that no study showed the efficacy of pharyngeal packing in terms of decreasing the incidence of PONV. 15 However, there were several problems with the analysis used in that review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Although pharyngeal pack is not universally adopted and is indeed rare in North America, 9 it has been a frequently used practice, especially in other European countries Turkey, Ireland, and so on as well as the United Kingdom, to minimize the risk of blood aspiration despite intubation cuff, as well as blood swallowing. 2,4 Previously, a review of pharyngeal pack usage for nasal surgery in 2009 assessed four randomized controlled trials and found that no study showed the efficacy of pharyngeal packing in terms of decreasing the incidence of PONV. 15 However, there were several problems with the analysis used in that review.…”
Section: Discussionmentioning
confidence: 99%
“…However, pharyngeal packing also has its own associated problems, such as postoperative throat pain. This adverse effect is thought to be due to the irritating characteristics of the packing material on the pharyngeal mucosa . The prevalence of sore throat following intubation varies from 14.4% to 50% and has been reported in up to 60% of cases when pharyngeal packs were applied .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Lami et al concluded that the use of throat packs does not confer PONV reduction benefit after nasal surgery in adult [ 9 ]. Postoperatively, patients filled out a validated questionnaire measuring degree of PONV and throat pain.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized controlled trial was conducted to investigate the association between the use of throat packs and postoperative PONV (postoperative nausea and vomiting) and treat pain after nasal surgery in adult patients [ 9 ]. This randomized controlled trial concludes that throat packs do not lower the risk of postoperative nausea and vomiting and are associated with more throat pain in the immediate recovery period after nasal surgery.…”
Section: Introductionmentioning
confidence: 99%